Analysis Determinants of Entrepreneurial Interest in the Traditional Cake Industry - Jatmiko Wahyu Nugroho; Fajriani Azis; Hajar Dewantara; Andika Isma (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2024)
This research aims to determine the factors that influence entrepreneurial interest in the traditional cake industry. Empirical study of traditional apang cake entrepreneurs in Datae, Lawawoi sub-district, Watang Pulu sub-district, Sidenreng Rappang district. This research is categorized as Quantitative Descriptive research with a population of 47 kiosks. Data obtained through distributing questionnaires with a Likert scale. The analysis technique used is quantitative analysis and multiple linear regression analysis. The results of the research show that the variables Internal Factors (X1) and External Factors (X2) have a positive and significant effect on Entrepreneurial Interest (Y) in Datae, Lawawoi Village, Watang Pulu District, Sidenreng Rappang Regency. The results of this research can be used as motivation for the community, especially housewives who have an interest in entrepreneurship, to start entrepreneurship in any field to develop creativity and fulfill family life.